Active Therapeutic and Diagnostic Management of Ascites of Unclear Etiology in a Patient With Tuberculosis - Z.R. Rashidov; Sh.T. Tirkashev; O.U. Rakhimov; Sh.A. Xudaybergeniv (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Ascites in women of reproductive age presents a complex diagnostic problem because it may arise from gynecological, oncological, infectious, or systemic diseases. Specific Background: Peritoneal and genital tuberculosis often show chronic and nonspecific manifestations that mimic other abdominal and pelvic disorders. Knowledge Gap: The absence of specific clinical and laboratory indicators frequently delays accurate identification of the etiology of unexplained ascites. Aims: This study describes a clinical case applying an active diagnostic approach to determine the cause of ascites in a reproductive-age woman with a history of disseminated tuberculosis, menstrual dysfunction, and infertility. Results: Diagnostic laparoscopy with ascitic fluid sampling and peritoneal biopsy revealed serous ascitic fluid, peritoneal hyperemia, and fibrinous deposits, while bacteriological and histological analyses showed a chronic inflammatory process without confirmation of tuberculous infection or malignancy. Novelty: The case demonstrates the clinical value of combining multidisciplinary evaluation with early invasive diagnostic procedures in unexplained ascites. Implications: Inclusion of peritoneal and genital tuberculosis in the differential diagnostic algorithm and the use of diagnostic laparoscopy can support accurate etiological clarification and guide therapeutic decision-making in tuberculosis-endemic regions. Highlights: • Multidisciplinary Evaluation Identified Chronic Inflammatory Origin Despite Suspected Tuberculous Etiology• Invasive Assessment With Peritoneal Biopsy Ruled Out Malignant Pathology in Persistent Abdominal Fluid Accumulation• Clinical Presentation Combining Infertility, Menstrual Disturbance, and Low-Grade Fever Complicates Etiological Identification Keywords: Ascites of Unclear Etiology, Diagnostic Laparoscopy, Peritoneal Tuberculosis, Genital Tuberculosis, Chronic Inflammatory Process.